Optimalisasi Kinerja melalui Self Leadership, Keterlibatan Kerja, dan Teamwork - Puspitasari, Ni Luh Ayu Novi; Suartina, I Wayan; Sunny, Milla Permata (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The performance determinants of every employee in the company must always receive serious attention from the Company. Performance will greatly determine the course of the company's operations to be able to maximize its resources. The purpose of this research is to find out self-leadership, work involvement and teamwork that have an impact on performance at PT. Little Island Property. The population is 85 people and all of them are used as samples. Research data were analyzed using multiple linear regression analysis method. The findings from this study, namely self-leadership, work involvement and teamwork show a positive and significant impact on performance. It is suggested to the company to continue to oPT.imize performance by increasing self-leadership, work involvement, and employee teamwork in the company.